Modified Candy-Package technique vs Cerclage technique for refixation of the lesser trochanteric fragment in pertrochanteric femoral fractures. A biomechanical comparison of 10 specimens. Issue 8 (August 2020) - Schopper, C.; Faschingbauer, M.; Moeller, R.-T.; Gebhard, F.; Duerselen, L.; Seitz, A.
Highlights: A second, subtrochanteric fixation point concerning the lesser trochanteric fragment significantly increases the withstanding against the force of the Iliopsoas muscle in pertrochanteric 3-part fractures. Novel biomechanical testing setup simulating the Iliopsoas muscle force with respect to the mechanical properties of the proximal femur. Simulation of a realistic postoperative scenario by use of human femora using a dynamic displacement evaluation in a common fracture scenario. Biomechanical comparison of a 2-point fixation method and a 1-point fixation concerning the lesser trochanteric fragment in pertrochanteric 3-part fractures. Abstract: Objectives: Separation of the lesser trochanteric fragment in pertrochanteric 3-part fractures leads to a significant weakening of the medial cortical wall. Because of the attachment of the Iliopsoas muscle to this structure, the lesser trochanteric fragment tends to cranial dislocation along this muscle's action direction. Refixation of these fractures using an intramedullary nail and an additional wiring osteosynthesis can be considered an operative standard. Based on an intramedullary osteosynthesis procedure, the question was raised whether a 2-point fixation method was favourable over a 1-point method regarding the pull-out resistance of the lesser trochanteric fragment against the Iliopsoas muscle's force. Methods: Based on an intramedullary osteosynthesis (PFNA, DePuy/Synthes/SUI), two groups á five human femora were defined depending on the refixation technique of the lesser trochanteric fragment (1-point supertrochanteric "Cable" vs 2-point super/subtrochanteric fixation " Candy-Package" performed with a 1.25-mm steel cerclage). The specimens were tested using a novel traction setup, simulating the activity pattern of the Iliopsoas muscle. The target value was the resistance of the refixated lesser trochanteric fragment against a defined pull-out force produced by the Iliopsoas muscle. The main parameters considered were the peak traction force (Fmax) and the maximum summative work (WFmax) at construct failure. Results: The Fmax and WFmax displayed a significant difference in favour of the Candy-Package (2-point super/subtrochanteric fixation) group (822 N vs. 476 N, 13.8 k Nmm vs 4.4 k Nmm, respectively; P = 0.01). Conclusions: The Candy-Package technique is a method that displays significantly more resistance than a single cerclage osteosynthesis regarding fragment loosening under the application of a simulated Iliopsoas muscle force in the course of a biomechanical proximal femoral 3-part fracture model.